Challenges and opportunities in biofuels production - Srinivas, Darbha; Satyarthi, Jitendra Kumar (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Biofuels are attractive alternative to petroleum diesel. They are renewable, non-toxic, biodegradable, carbon neutral and lead to reduced tailpipe emissions. This article presents the current state-of-art processes of their production and discusses the opportunities and future challenges in this area of research.
Keywords: Biodiesel; biofuels; Deoxygenation; Hydrotreatment; Renewable fuels; Solid catalysts; Transesterification (fatty acid glycerides); Vegetable oils/fats